A 37 GHz millimeter-wave antenna array for 5G communication terminals - Ullah, Sadiq; Khan, Jalal; Ali, Usman; Matekovits, Ladislau; Ahmad Tahir, Farooq; Abbasi, Muhammad Inam (Tech Science Press, 2023)
This work presents, design and specific absorption rate (SAR) analysis of a 37 GHz antenna, for 5th Generation (5G) applications. The proposed antenna comprises of 4-elements of rectangular patch and an even distribution. The radiating element is composed of copper material supported by Rogers RT5880 substrate of thickness, 0.254 mm, dielectric constant (εr), 2.2, and loss tangent, 0.0009. The 4-elements array antenna is compact in size with a dimension of 8 mm × 20 mm in length and width. The radiating patch is excited with a 50 ohms connector i.e., K-type. The antenna resonates in the frequency band of 37 GHz, that covers the 5G applications. The antenna behavior is studied both in free space and in the proximity of the human body. Three models of the human body, i.e., belly, hand, and head (contain skin, fat, muscles, and bone) are considered for on-body simulations. At resonant frequency, the antenna gives a boresight gain of 11.6 dB. The antenna radiates efficiently with a radiated efficiency of more than 90%. Also, it is observed that the antenna detunes to the lowest in the proximity of the human body, but still a good impedance matching is achieved considering the −10 dB criteria. Moreover, SAR is also being presented. The safe limit of 2 W/kg for any 10 g of biological tissue, specified by the European International Electro Technical Commission (IEC) has been considered. The calculated values of SAR for human body models, i.e., belly, hand and head are 1.82, 1.81 and 1.09 W/kg, respectively. The SAR values are less than the international recommendations for the three models. Furthermore, the simulated and measured results of the antenna are in close agreement, which makes it, a potential candidate for the fifth-generation smart phones and other handheld devices.